Assessment of frequency and duration of point counts when surveying for golden eagle presence. (15th June 2017) - Skipper, Ben R.; Boal, Clint W.; Tsai, Jo‐Szu; Fuller, Mark R.
ABSTRACT: We assessed the utility of the recommended golden eagle ( Aquila chrysaetos ) survey methodology in the U.S. Fish and Wildlife Service 2013 Eagle Conservation Plan Guidance. We conducted 800‐m radius, 1‐hr point‐count surveys broken into 20‐min segments, during 2 sampling periods in 3 areas within the Intermountain West of the United States over 2 consecutive breeding seasons during 2012 and 2013. Our goal was to measure the influence of different survey time intervals and sampling periods on detectability and use estimates of golden eagles among different locations. Our results suggest that a less intensive effort (i.e., survey duration shorter than 1 hr and point‐count survey radii smaller than 800 m) would likely be inadequate for rigorous documentation of golden eagle occurrence pre‐ or postconstruction of wind energy facilities. Results from a simulation analysis of detection probabilities and survey effort suggest that greater temporal and spatial effort could make point‐count surveys more applicable for evaluating golden eagle occurrence in survey areas; however, increased effort would increase financial costs associated with additional person‐hours and logistics (e.g., fuel, lodging). Future surveys can benefit from a pilot study and careful consideration of prior information about counts or densities of golden eagles in the survey area before developing a survey design. If information is lacking, survey planning may be best served by assuming low detection rates and increasing the temporal and spatial effort. Published 2017. This article is a U.S. Government work and is in the public domain in the USA. Abstract : To improve survey methodology for golden eagles in context of wind energy development, we assessed the influence of temporal duration, frequency, and spatial scale of surveys. We found that survey durations shorter than 1 hr and point‐count survey radii smaller than 800 m would likely be inadequate for rigorous documentation of golden eagle occurrence pre‐ or postconstruction of wind energy facilities.